2015
DOI: 10.1007/s11356-015-5536-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiosuppressive properties of marine-derived compounds—a mini review

Abstract: Angiogenesis, formation of new blood vessels from preexisting one, is a critical step of tumorgenesis of solid tumors. Therefore, antiangiogenic therapy is one of the promising approaches to control tumor growth. In the past 20 years, a lot of compounds have been tested for their antiangiogenic properties. Bevacizumab, Avastin, the first antiangiogenic drug approved by the US FDA, has been widely used in clinic for treating cancer. Indeed, many synthetic compounds are highly toxic and exert side effects even t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Thus, the inhibition of this process could suppress tumor progression. Previous studies have shown that many marine-derived substances can display inhibitory effects on new vessel development (66). This work showed that Fx failed to prevent HUVEC migration in the presence of GBM1 cells.…”
Section: Conditioned Medium Of Fucoxanthin Treated-gbm Cells Inhibite...mentioning
confidence: 66%
“…Thus, the inhibition of this process could suppress tumor progression. Previous studies have shown that many marine-derived substances can display inhibitory effects on new vessel development (66). This work showed that Fx failed to prevent HUVEC migration in the presence of GBM1 cells.…”
Section: Conditioned Medium Of Fucoxanthin Treated-gbm Cells Inhibite...mentioning
confidence: 66%
“…Marine organism has evolved chemical means in order to defend themselves against the complex environment ( Gammone et al 2016). Such chemical and biological adaptation generates structural diversity of compounds with various biological activities and potential anticancer effect (Yue et al 2017). Up to 2012, more than 22,000 natural products from marine source have been reported (Gerwick and Moore 2012).…”
Section: Discussionmentioning
confidence: 99%